(untitled) (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
In South Korea, Technology education is one of the national curriculum compulsory subjects, and despite the importance and value, public awareness toward technology and technology education is very low. Whenever the curriculum is revised, the value and place of technology education have been challenged. The purpose of this study is to analyse effects on students of technology education classes. Meta-analysis is conducted to calculate the effect size of technology education classes in the Republic of Korea. Data are collected through an integrated searching engine of Korean academic database. From 2000 to 2022, 61 studies are analysed by Comprehensive Meta Analysis 4.0. The result shows an intermediate effect size in technology education classes. A total of 148 effect sizes are analysed by dividing the subcategories into publishing type, teaching method, school level, experimental type, and dependent variable. For the publishing type, academic journals and thesis papers show the intermediate effect size. Particularly, studies for elementary school level indicate a high effect size, followed by middle school and high school. The dependent variables show intermediate effect sizes of the order of affective variables (e.g., attitude, motivation), psychomotor variable, and cognitive variables (e.g., academic achievement). Based on the findings, this study can make the following recommendations. More studies for proving the value and importance of technology education classes should be conducted. Key Word : Technology Classes, Effect Size, Meta-analysis, Students, South Korea